(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the home health care needs of outpatients at Quynh Mai and to analyze factors related to these needs of studied outpetients. Subjects and methods: The study was conducted on 100 outpatients at the Quynh Mai ward Health Station, from January to March 2025. A cross-sectional design was crried out. Patient’s information was collected by using direct interview technique based on a pre-written questionnaire and using available data from health records at the health station. Data were processed and analyzed by using SPSS version 26.0. Results: Among studied outpetients, 90% are female, 70% are ≥ 65 years old and on education level, 72% of them are high school or over. The rate of outpetients expressing a need for home health care was 77%. Marital status was a factor associated with the need for home health care (married outpetients have a higher need for home health care than single/divorced outpetients (79.2% vs. 25%, p = 0.012, OR = 11.4). Conclusion: The study shows that the need for home health care of outpatients at Quynh Mai ward is 77%; marital outpatients have a higher need for home health care than single/divorced outpatients (79.2% vs. 25%, p = 0.012, OR = 11.4).